Differential impact of hypothalamic and hippocampal corticotropin-releasing hormone neurons on stress, cognition, and seizure susceptibility - Hooper, Andrew. (2017)
Abstract: Proper regulation of the hypothalamic-pituitary-adrenal axis permits the adaptive, integrated response to stress. Corticotropin-releasing hormone neurons in the paraventricular nucleus of the hypothalamus reside at the apex of this stress signaling axis, so any genetic or environmental insult to the normal modulation of their activity can profoundly disrupt healthy stress signaling. Additionally, there exist corticotropin-releasing hormone neurons in other brain regions, notably the hippocampus. Much less is known about the function of this population, but it is thought to be critical for stress effects on cognition. The main focus of my thesis work has been twofold: first, to investigate the cellular mechanisms that regulate the activity of hypothalamic corticotropin-releasing hormone neurons involving robust inhibitory constraint by GABA and the rapid erosion of inhibition; and second, to explore the characteristics and functional relevance of hippocampal corticotropin-releasing hormone neurons, with particular emphasis on their stress-reactivity and impact on the excitability of the hippocampal network. The relatively recent advent of genetic tools to isolate specific cell types in the brain for identification and manipulation provided the foundation for my investigations of these two neuronal populations: specifically, a transgenic mouse line that expresses Cre recombinase under the control of the promoter for the corticotropin-releasing hormone gene. For my investigations in the hypothalamus, I combined this line with a Cre-dependent mouse line that abolishes the chloride-extruding capacity of KCC2, in order to generate a mouse model exhibiting impaired inhibitory constraint of the neuroendocrine stress response, enabling me to study stress-related physiology and behavior which depend on this inhibitory constraint. For my investigations in the hippocampus, I combined the Cre recombinase line with a number of Cre-dependent molecular tools, including tracer viruses to study anatomical connectivity, the light-activated cation channel Channelrhodopsin to study functional connectivity and circuit-level effects, and Designer Receptors Exclusively Activated by Designer Drugs to study effects of manipulating this population's activity on hippocampal-dependent behavior and seizure susceptibility. I confirmed that inhibitory constraint of hypothalamic corticotropin-releasing hormone neurons is critical for regulating stress-reactive emotional behaviors, and helped to reveal that this inhibitory constraint is compromised following seizures. Unexpectedly, I also uncovered a novel projection from the hypothalamic population to the tuberal nucleus of the lateral hypothalamus, as well as a possible functional role for this population in body weight homeostasis. In the course of my hippocampus-oriented project, I characterized back-projecting corticotropin-releasing hormone neurons as a novel interneuron population. In addition to extensively characterizing the intrinsic properties of this population, I also uncovered their functional relevance in hippocampal-dependent learning and memory, excitability of the hippocampal network, and seizure susceptibility. My results from studying hypothalamic chloride plasticity helped to identify a mechanism that gives rise to the vicious cycle of mutual reinforcement between pathological stress and seizures. This mechanism highlights KCC2 as a drug target with great potential for alleviating stress-related disorders and seizures, and breaking the vicious cycle between them. My characterization of back-projecting CRH interneurons adds another layer of complexity to the circuitry of the hippocampus. Additionally, my findings on CRH interneurons' impact on both the physiological function of learning and memory, and the pathophysiology of seizure susceptibility, highlight the importance of this interneuron class in hippocampal function. Finally, my results on the circuit-level impact of manipulating these interneurons provide the beginning of a mechanistic framework for how this single cell type contributes to a complex behavior, while raising exciting new questions about the differential effects of synaptic versus peptidergic transmission.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Neuroscience.; Advisor: Jamie Maguire.; Committee: Maribel Rios, Stephen Moss, Leon Reijmers, and Kerry Ressler.; Keyword: Neurosciences.